FIRING GUN AS AN ENTHUSIASIM FACTOR OF WEDDING TRADITION IN GİRESUN AND ITS NEIGHBORHOODS - Çağatay KARADENİZ (Fırat University, 2019)
It needs to be stated that all social layers have influence on Turkish culture. Specially, the place of Turkish family and cultural circle taking shape around it on our centuries- old culture has been continuously wondered. Turkish family should be mentioned in the studies concerning our cultural life since Turkish family is at the core of Turkish culture. It is not known when Turkish cultural factors come into existence in Giresun and its neighborhoods. However, the studies on this issue take us back thousand of years. In the light of scientific researches done in rural areas of Giresun, it should be underlined that the region contains a great variety of cultural elements. In folklore studies, it is possible to recognize various cultural elements such as literal, religious, historical, social, and musical elements in this region. Especially, the rituals concerning wedding ceremonies in Giresun comprise of various historical richness. Firing guns and the yells during the wedding contain several cultural values. We consider that it will be beneficial to draw attention to some sociologic and folkloric themes in an attempt to determine and evaluate these cultural values. In this way we are of the opinion that the data obtained will be convenient for interdisciplinary content and will be more comprehensive to explain cultural values presented by our study. This study analyzes the socio-cultural effects of the enthusiasm arising from local instrument and music, especially, in village weddings. Moreover, area study and interviews will be utilized to complete the study.